To the History of the Russian Foreign Press: “Ukhvat” Magazine - Elena R. Obatnina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
Based on previously unknown archival materials, the article reconstructs the history of the creation of the first emigrant satirical magazine “Ukhvat”. The subject matter were peculiarities of the printed organ’s ideological and literary program, formed on the initiative of the Russian Montparnasse’s representative — the poet D.Yu. Kobyakov, and with the participation of A.M. Remizov and M.A. Osorgin which were well-known writers. They formed an informal editorial board, which actually determined the publication’s program. The article contains new data for the creative biography of the journal’s leaders. The published material allows us to trace the specific nuances of the journal’s program in the context of the Russian emigration and in the interpretation of its editor Kobyakov, who returned to the USSR in 1958. In the history of the Russian foreign press, “Ukhvat” remains a publication that reflects the mentality of representatives of the Russian diaspora, humorous escapades of both famous literary masters and authors hiding under pseudonyms were published.